RECENT ADVANCES IN OPTIMIZATION AND MAXIMIZATION OF ARTEMISININ YIELD FOR ARTEMISININ BASED COMBINATION THERAPY - SUGANDHA TIWARI (International Journal of Pharma and Bio Sciences, 2012)
According to WHO artemisinin based combination therapy (ACT) is the only reliable treatment option for multidrug resistant Plasmodium falciparum malaria and to control the spread of the disease under its global malaria eradication programmes. Artemisinin is a sesquiterpene lactone endoperoxide isolated from Artemisia annua plants belonging to family Asteraceae. Artemisinin and its derivatives are found to be effective against schistosomiasis, breast cancer, human lukaemia, colon cancer and lung carcinomas. Low yield of artemisinin in A. annua plants (0.01-0.8%, in some strains 1.5%) is a serious limitation to meet the annual targets of the drug (approximately 115-135 tonnes) for ACT treatments. The present review covers the biosynthesis of artemisinin and various approaches to increase artemisinin content in A. annua plants and new researches on heterologous expression systems.